Trends in Hepatocellular Carcinoma among Hepatitis C Patients Achieving Sustained Virological Response Following Direct-Acting Antivirals Treatment - Ummi Maimunah (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy)
-